A probabilistic analysis technique for single event transient sensitivity evaluation of phase-lock-loops. (September 2019) - Duoli, Li; Chuanbin, Zeng; Wei, Dou; Linchun, Gao; Weiwei, Yan; Bo, Li; Yang, Huang; Tao, Liu; Long, Xing; Hainan, Liu; Jiajun, Luo; Zhengsheng, Han
Abstract: This paper proposes a probabilistic analysis technique to evaluate the single event transient sensitivity. Using the technique in both the time domain and spatial domain, Single-Event Transients (SET) sensitivity of a Phase-Locked-Loop (PLL) designed for SET mitigation has been analyzed as an example. Statistical results of simulation can figure out the SET sensitive nodes, which are validated by laser experiment of PLL chip fabricated with high voltage process (3.3 V) of a 90 nm PDSOI baseline.